Multiple Intelligences In The Development Of Expository Writing Production Of Eight Grade Students In A Private Institution (2016)
Nowadays in the globalized society in which we lived it is important to acquire, master and know how to teach a foreign language. For this reason, the current action research sought to improve the expository writing production in a foreign language (English). In a private institution, specifically in an eighth gradefrom Armenia – Quindío, through the implementation of different workshops based on multiple intelligences. In order to achieve the former previously stated the following procedure was done: First of all it was mandatory to define multiple intelligences theory taking as a reference Jie-qi-chen and Howard Gardner to define both multiple intelligence theory and verbal, inter- personal and intra personal intelligence.Second, in order to improve the writing production it was mandatory to implement several workshops based on multiple intelligences and finally a final test so as to reinforce and teach not only the expository text structure but also the use of some grammatical rules. The data was analyzed using data triangulation and grounded theory and it was found out that Multiples Intelligences allowed students to be competent in writing, to internalized structures and to write coherently.